2019
DOI: 10.1021/acssuschemeng.9b04026
|View full text |Cite
|
Sign up to set email alerts
|

Polyoxometalate-Based Poly(ionic liquid) as a Precursor for Superhydrophobic Magnetic Carbon Composite Catalysts toward Aerobic Oxidative Desulfurization

Abstract: The dispersity of heterogeneous catalysts in solid–liquid biphase reactions is of great importance to their catalytic performance. Herein, superhydrophobic magnetic carbon composite catalysts were synthesized by calcination of magnetic polyoxometalate-based poly­(ionic liquid). The magnetic poly­(ionic liquid) not only served as the carbon and Mo sources and reductant but also made MoO x uniformly disperse on the surface of amorphous carbon. The superhydrophobic catalyst MoO x /MC-600 with a calcining tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(38 citation statements)
references
References 49 publications
2
36
0
Order By: Relevance
“…Carbon is a type of excellent supporter for catalysts and its precursor can combine with metal to form a carbon‐supported catalyst with homogeneous dispersion of the active site. Jiang et al reported that carbon‐supported MoOx catalyst prepared with polyoxometalate‐based PIL as precursor showed outstanding catalytic property for ODS . However, few research reports desulfurization of fuel oil with vanadium‐based catalysts loading on carbon because of shedding catalyst.…”
Section: Introductionsupporting
confidence: 69%
“…Carbon is a type of excellent supporter for catalysts and its precursor can combine with metal to form a carbon‐supported catalyst with homogeneous dispersion of the active site. Jiang et al reported that carbon‐supported MoOx catalyst prepared with polyoxometalate‐based PIL as precursor showed outstanding catalytic property for ODS . However, few research reports desulfurization of fuel oil with vanadium‐based catalysts loading on carbon because of shedding catalyst.…”
Section: Introductionsupporting
confidence: 69%
“…To get insight into the effect of the (Gly) 3 PMo 12 O 40 @MnFe 2 O 4 hybrid dosage on the Cat‐ODS process, the catalytic oxidation tests were developed in the catalyst dosage range of 0‐0.12 g (Figure 7). As expected, the Cat‐ODS efficiency of all types of organosulfur compounds in MFOs was sharply increased after increasing the catalyst dosage from 0.03 to 0.10 g. It is caused by the high production of oxoperoxo‐metal complexes in the reaction medium 48‐51,53 . These highly reactive complexes are the key intermediates in the conversion of Th, BT, and DBT molecules to their corresponding sulfoxides and sulfones.…”
Section: Resultssupporting
confidence: 51%
“…Interestingly, among the different Keggin‐type POMs, it can be noted that the phosphorus‐centered structures have a tremendous potential to be more active than their silicon analogs due to the formation of more stable oxoperoxo‐metal complexes in Cat‐ODS reactions 53 . By comparing the results of the current survey with earlier literature, it can be also concluded that the synthesized (Gly) 3 PMo 12 O 40 @MnFe 2 O 4 hybrid nanocomposite shows the extraordinary performance in the oxidation of Th, BT, and DBT under the mild reaction conditions (at the temperature of 35°C and reaction time of 60 minutes) 6,20,39,48‐51 …”
Section: Resultsmentioning
confidence: 58%
“…Jiang et al prepared two kinds of magnetic catalysts (IL/MMS-S and IL/MMS-L) by the immobilization of ionic liquid [(C 18 H 37 ) 2 (CH 3 ) 2 N] 3 PW 12 O 40 on the small core-shell magnetic mesoporous silica (MMS-S) or large core-shell magnetic mesoporous silica (MMS-L) microspheres and tested their catalytic performance for the oxidative desulfurization of diesel fuel with H 2 O 2 ( Jiang et al, 2019b ). Compared with the catalyst IL/MMS-L, the small size catalyst IL/MMS-S showed superior catalytic activity in the oxidative desulfurization, and the 4,6-DMDBT removal with the sulfur content decreasing to 9.2 ppm ( Supplementary Figure S21 ).…”
Section: Deep Oxidative Desulfurizationmentioning
confidence: 99%